ANALISIS PERBANDINGAN PENGGUNAAN BAHAN BAKU UNTUK MENENTUKAN EFISIENSI BIAYA - Qur’any, Vidyas Anjarisma; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research has been carried out at PT. Rendjani Metalindo which is the manufacture of mechanical chairindustry in which its primary raw material is steel sheet and the source of purchase is import. This research ismeant to find out which one of the costs of raw material is more efficient in using imported and local rawmaterial. In general, the decision making of the purchasing of raw material on manufacturing companies ismeant to minimize the cost and to maximize the profit in a certain period. To carry out the research, qualitativemethod and primary and secondary data collection technique i.e. observation, interview, and documentation atPT. Rendjani Metalindo have been applied in this research. The data analysis technique has been carried out byusing descriptive analysis in which the cost efficiency of raw materials can be determined by comparing the totalcost of use of imported and local raw material. The result of the research shows that 18.26% efficiency has beengained by using local raw materials when it is compared to the use of imported raw material. One of the factorswhich gives influence to the efficiency of local raw material is that there is no surcharge element in purchasing.The high cost of imported raw material occurs due to import duty, article 22 income tax, freight forwarding,local transportation, and anti-dumping cost which is beared by the company during the occurrence ofpurchasing process.Keywords: Cost efficiency, Imported raw material, Local raw material, Decision making.